(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
In this article review and the analysis of the basic standards of video which can be used for transmission of the multimedia information on 4G-networks are executed; also comparison of key parameters which influence on efficiency of the standard is resulted.